Women Entrepreneurship and Empowerment in Hospitality Industry: A Systematic Literature Review - Vinoja, S.; Kamalakumari, K. (University of Vavuniya, 2022)
The hospitality industry is one of the significant sectors all across the world. Women entrepreneurs are a developing section of businesses in the hospitality industry due to their contribution to food stalls little eateries, and their caring nature service. This study to bring out the obstacles, attributes, and performance inhibitors of women entrepreneurs, conducted a systematic review of the literature on women entrepreneurs in the hospitality industry. This study is based on analyzing a total of 30 articles directing attention to women entrepreneurs in the hospitality industry, published between 2004 and 2021. The current study reveals three themes: obstacles significant for women entrepreneurs, their attributes, and factors that influence their performance and support their prosperity in the hospitality industry. Since the study is based on a literature survey, the systematic literature review was used as a methodology to address the research question: what are the obstacles, attributes, and contributing factors to the success of women entrepreneurs in the hospitality industry. The findings of the literaturo survey highlighted that the major obstacles that are remarkable for women entrepreneurs in the hospitality industry are maintaining a decent balance between work and day-to-day life is a main pressing issue, and working women specifically feel the difficulties of attempting to keep up with such a balance; women entrepreneurs are extraordinarily influenced by culture and social norms; women regularly experience ill effects of low validity while managing the different partners related with their firm (like providers, clients, and investors); socio-economic limitations have restricted women's admittance to a significant business experience; family commitments hindered professions. As found in the literature survey, the entrepreneurial attributes of women entrepreneurs in the hospitality industry are; 1) They are intentionally or unknowingly ready to sacrifice development and stay away from unacceptable risks 2) Traditions, religion, identity, educational attainment, and marital status join to construct the capacity and eagerness of women to turn into entrepreneurs 3) women entrepreneurs were inspired by economic development, work creation, and the conveyance of wellbeing-focused administrations and products 4)Their business achievement has been attached to their obligation to improve the local area. Appropriate support and consolation from the general public, family, and government; self-confidence; self-initiative qualities; and financial autonomy are the most important factors to female entrepreneurial business success in the hospitality industry. Moreover, the researchers propose a step-by-step instruction to foster the business utilizing restricted assets and financial capital.
Keywords: Attributes; Obstacles; Hospitality industry; Women entrepreneurship